(untitled) (Delta Medical College Journal, 2015)
Background: Cancer is a major health burden worldwide. By 2030, over 9 million cancer patients are assumed to die in developing countries from different types of cancers. Incidence of different types of cancers is increasing due to unhealthy life style. At present, lung cancer is most prevalent in Bangladeshi male whereas it is cancer cervix in female. Objective: To determine the frequency, pattern and treatment modalities in different types of cancer in different age and sex group to get an idea about national cancer scenario. Materials and method: A cross-sectional study was conducted on 1300 cancer patients attending at Delta Medical College Hospital within three months duration (from 15.07.10 to 15.10.10). Histologically proven malignant cases were included in the study. Results: There were 400 male and 900 female patients. Male: female ratio was 1:2.25. Among all patients, cervical cancer was the top most common malignancy (23.07%) followed by breast (22.46%). In male, lung cancer was found to be the most common cancer (15.75%), followed by non-Hodgkins lymphoma (13.75%), colorectal (12%), stomach (6.75%), and oesophageal (5.75%) carcinomas. In female patients, carcinoma cervix was the top most cancer (33.33%), followed by breast (32.33%), ovary (6.11%), gall bladder (3.77%), and colorectal (3%) carcinomas. Majority of cancers occurred in middle and older age groups. Combination of surgery, chemotherapy and teletherapy was the most common form of treatment. Conclusion: The findings of the study may provide a helpful clue to important facts and figures of different types of cancers in Bangladesh. Delta Med Col J. Jul 2015; 3(2): 57-62